Molecular Diversity of Diplostomum spathaceum (Digenea: Diplostomidae) on the Capoeta umbla and Cyprinus carpio (Cypriniformes) Using Mitochondrial DNA Barcode - Barata, Sibel Dogan; Dorucu, Mustafa; Saglam, Naim; Gurses, Murad; Otlu, Onder (Central Fisheries Research Inst, 2023)
Diplostomid trematodes (Digenea) include a wide and diverse group of common digeneans. Diplostomid larval stages are significant pathogens that may exert grave effects on both natural fish and aquaculture populations. Diplostomum species, which use fish as a second intermediate host, is one of the most common trematode species, which affects the fish welfare negatively with the formation of cataracts by settling in the eye. This study is determined the molecular characterization of Diplostomum parasite in Cyprinus carpio and Capoeta umbla for the first time from Turkey, based on the mitochondrial COX1 sequence data. Diplostomum samples were determined as Diplostomum spathaceum according to the phylogenetic trees created in the light of the morphological and COX1 sequence data. Sequence results matched similar to 98-100% with D. spathaceum as a result of blast analysis. It was defined that this parasite was represented by three different haplotypes in Turkey. As a result of haplotype analysis performed on a total of 162 isolates in GenBank and obtained in this study, 40 polymorphic regions and 58 haplotypes were determined. This haplotype network had arranged within a star-like configuration with a main central haplotype. This shows that the variation within D. spathaceum species is quite high. The mean abundance, mean intensity, and prevalence of the parasite in C. carpio were 8.29 (5.80-11.24), 10.91 +/- 9.37 (1-39), and 76%, respectively. In the C umbla, mean abundance, mean intensity, and prevalence were calculated as 11.54 (10.16-12.92), 14.07 +/- 16.59 (1-67), and 82%, respectively.
Keywords: Fish eyes parasites; Diplostomum spathaceum; Cytochrome c oxidase subunit I (COX1); Genetic variation; Biodiversity